2014
DOI: 10.5121/ijbb.2014.4401
|View full text |Cite
|
Sign up to set email alerts
|

Novel Adaptive Filter (NAF) for Impulse Noise Suppression from Digital Images

Abstract: In general, it is known that an adaptive filter adjusts its parameters iteratively Peak-Signal-to-Noise Ratio (PSNR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It has been observed that the window sizes needed for 10% to 90% noise density range between 3 to 9. Table 2 shows the better performance of the proposed NAF over the filter schemes described in [12], [17], [18] and [22] for low to high noise density cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the window sizes needed for 10% to 90% noise density range between 3 to 9. Table 2 shows the better performance of the proposed NAF over the filter schemes described in [12], [17], [18] and [22] for low to high noise density cases.…”
Section: Resultsmentioning
confidence: 99%
“…A Novel Median Filter (NMF) presented in [22] addresses the task of impulsive noise cleaning from the noisy grey scale images and aims at effectively suppressing the impulse noise while preserving the edge information intact. Proposed scheme is simple and yields better denoising performance with better detail preserving up to 60-70% noise densities, but fails to perform well at higher noise situations.…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly used vector filters for noise removal in color images are the Vector Directional filter (VDF) [24] and the Directional Distance Filter (DDF) [25], Vector Median Filter (VMF) and those reported in [26], [27], [28] and [29]. It is also observed that the use of fixed value of threshold is not the ultimate solution for denoising of different types of images and ideally it should be changed adaptively according to the contents of the filtering window [9], [15], [16], and [18]. In this paper, we present an impulse detection method where the decision threshold is dynamic and adaptively changes on the basis of pixel statistics within the filtering window.…”
Section: Introductionmentioning
confidence: 99%
“…Filtering of only noisy pixels results into better preservation of detail features. Most of the impulse detection methods available in the literature require a decision threshold value [16], [17] and [21] to make an intelligent decision whether the pixel under consideration is noisy or not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation